Causal association between systemic lupus erythematosus and the risk of migraine: A Mendelian randomization study - Meixuan Ren; Hangtian Yu; Bing Xiao; Yan Zhao; Jiewei Yan; Jianghong Liu (Brain and Behavior, 2024)
Abstract Background Numerous studies have found that patients with systemic lupus erythematosus (SLE) often have comorbid headache, especially migraine. However, the causal relationship between genetically determined SLE and migraine risk remains unclear. Therefore, we conducted a Mendelian randomization (MR) study to explore this causal association. Methods Genome‐wide association studies (GWAS) provided the instrumental variables. We selected summary data from GWAS of SLE as exposure (5201 SLE patients and 9066 controls). Both outcome GWAS data were from the Finnish Gene GWAS, including migraine with aura, migraine with aura and triptan purchases, and migraine without aura. The main MR approach was inverse‐variance weighted. Pleiotropy and heterogeneity were detected using the MR pleiotropy residual sum and outlier, MR‐Egger intercept test, leave‐one‐out analysis, and Cochran's Q test. Results There was a significant association between genetically predicted SLE susceptibility and increased risk of migraine with aura [odds ratio (OR) = 1.05, 95% confidence interval (CI) = 1.02–1.08, p = .001]. The result was consistent when the outcome was migraine with aura and triptan purchases [OR = 1.05, 95% CI = 1.02–1.08, p = .001]. However, we found no association between SLE and migraine without aura. Our MR study showed no pleiotropy or heterogeneity. Conclusions Our study indicates that genetic susceptibility to SLE increases the incidence of migraine with aura but not migraine without aura. It is necessary for the routine evaluation and early recognition of migraine in patients with SLE in clinical settings.